Peran Kegiatan Membaca Buku Self-Help dalam Meningkatkan Kesadaran Kesehatan Mental Siswa Sekolah Menengah: Tinjauan Literatur - Namira Nurul Dania; Moudy Aurelia Jessica; Ichsan Fauzi Rachman (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to examine the role of reading self-help books in enchancing mental health awareness among secondary school students. The background is based on various mental health challenges faced by adolescents, such as academic pressure, physical and hormonal changes, and complex social dynamics exacerbated by the COVID-19 pandemic. The method used is a literature review analyzing relevant national and international studies. The findings indicate that independent reading of self-help books can improve mental health literacy, self-efficacy, stress management, and emotional regulation among students. Futhermore, cultural adaption and reflective guidance are important to maximize the effectiveness of this intervention. The implications of this study affirm that self-help books can be an effective tool in school-based mental health literacy programs, but structured support and collaboration among psychologists, educators, and students are necessary to achieve optimal outcomes. Thus, this approach can help reduce stigma and increase awareness and magement of mental health among adolescents.